1995
DOI: 10.1056/nejm199507133330201
|View full text |Cite
|
Sign up to set email alerts
|

Amiodarone in Patients with Congestive Heart Failure and Asymptomatic Ventricular Arrhythmia

Abstract: Although amiodarone was effective in suppressing ventricular arrhythmias and improving ventricular function, it did not reduce the incidence of sudden death or prolong survival among patients with heart failure, except for a trend toward reduced mortality among those with nonischemic cardiomyopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
402
4
34

Year Published

1999
1999
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,095 publications
(445 citation statements)
references
References 27 publications
5
402
4
34
Order By: Relevance
“…One of the randomized trials demonstrated that the mortality and quality of life in NICM patients with a reduced LVEF were similar between those receiving amiodarone, and those with an ICD implantation for nonsustained VT 3. Although anti‐arrhythmic drug therapy has never been clearly shown to reduce SCD in NICM patients experiencing life‐threatening VAs, amiodarone, rather than sodium channel blockers, reduces the occurrence of VAs without the expense of an increase in the mortality in patients with postmyocardial infarction and heart failure 35, 36. In patients with an ICD implantation, amiodarone, especially in conjunction with beta‐blockers, significantly reduces ICD interventions 37.…”
Section: Management Of Vt In Nicmmentioning
confidence: 99%
“…One of the randomized trials demonstrated that the mortality and quality of life in NICM patients with a reduced LVEF were similar between those receiving amiodarone, and those with an ICD implantation for nonsustained VT 3. Although anti‐arrhythmic drug therapy has never been clearly shown to reduce SCD in NICM patients experiencing life‐threatening VAs, amiodarone, rather than sodium channel blockers, reduces the occurrence of VAs without the expense of an increase in the mortality in patients with postmyocardial infarction and heart failure 35, 36. In patients with an ICD implantation, amiodarone, especially in conjunction with beta‐blockers, significantly reduces ICD interventions 37.…”
Section: Management Of Vt In Nicmmentioning
confidence: 99%
“…[7][8][9] Sotalol is not recommended in the overt HF population given its negative inotropic and proarrhythmic potential.…”
Section: Recommendations For Antiarrhythmic Drug Selectionmentioning
confidence: 99%
“…Singh et a1. 62 found no significant effect of lowdose amiodarone on sudden death or overall mortality, although there appeared to be a favorable trend toward survival benefit in the treatment of DCM. In smaller trials examining both ischemic and DCM populations, the use of amiodarone significantly reduced ventricular ectopy on ambulatory ECG m0nitoring,6~.…”
Section: Am I Od a Ro N Ementioning
confidence: 75%